Prostate stem cell antigen and cancer risk, mechanisms and therapeutic implications. Issue 1 (January 2014) - Yang, Xueling; Guo, Zhi; Liu, Ya; Si, Tongguo; Yu, Haipeng; Li, Bo; Tian, Wei
Abstract : Prostate stem cell antigen (PSCA) was originally identified as a tumor antigen in prostate cancer. Recent studies indicated that PSCA was correlated with many cancer types. In this review, we will consider the origin of PSCA, discuss the expression of PSCA in normal and cancer tissue, describe PSCA polymorphisms and cancer risk, summarize potential mechanisms for PSCA involvement in cancer; and look into the therapeutic implications of PSCA. PSCA is upregulated in prostate cancer, pancreatic cancer and bladder cancer, as well as a number of others, making it an ideal clinical target for both diagnosis and therapy. Future studies will be required to explore its mechanisms on various cancer types, and to confirm its clinical utility for diagnosis and immunotherapy strategies. The study of PSCA regulation and expression may also provide information on normal prostate development and prostate carcinogenesis.